State capitalism, capitalist statism: Sovereign wealth funds and the geopolitics of London's real estate market. (May 2023) - Ward, Callum; Brill, Frances; Raco, Mike
We respond to the special issue's call for a multiscalar, historicised approach to state capitalism through an exploration of Sovereign Wealth Fund investment into London real estate. We point to how the UK's ostensibly market-led recovery since the 2008 financial crisis has relied in part on attracting 'patient' state capitalist investments. In this, we contextualise the relational regulation of real estate markets as the outcome of intersecting state projects by considering the investment motivations of the single largest owner of London real estate, the Qatari Investment Authority, and the utilisation of their investment by UK governance actors. Focusing on Qatari Investment Authority's involvement in London's Olympic Village, we highlight how this strategic coupling in the real estate market realised domestic and geopolitical aims for the Qataris while facilitating the UK government's strategy to ameliorate London's housing shortage by fostering a 'build to rent' asset class. In doing so, we contribute to readings of state capitalism as an 'uneven and combined' process beyond the traditional state/market binary by placing sovereign wealth fund investment into the context of city governance, the geopolitics of real estate and resultant relational forms of regulation.